A process-based competence evaluation for evidence-based dissemination (PROCEED): a study protocol - Simone Gorinelli; Essi Sairanen; Stefan G. Hofmann; Joseph Ciarrochi; Martti T. Tuomisto; Katariina Keinonen (BMC Psychology)
Abstract Background Despite extensive training to ensure high competence among psychologists and psychotherapists, scientific evidence directly linking therapist competence to treatment success remains limited. Existing competency evaluation methods often rely on subjective self-assessments or external ratings of natural therapy sessions, which are influenced by client characteristics and session context. Grounded in process-based therapy (PBT), this study aims to develop and validate a novel video-based tool (process-based competence task, PBCT) for assessing psychotherapeutic competencies. Method The validation of the tool will consist of two phases to ensure sensitivity to previous training and responsiveness to further training. First, sensitivity of the PBCT to prior training will be assessed by comparing the performance in the task in three groups (n = 240): psychology university students, psychotherapists in training, and psychotherapists. Second, the responsiveness of the PBCT to further training will be assessed among psychotherapist trainees and psychology students after a follow-up period (n = 160). Finally, the study will examine the impact of therapist competence on treatment outcomes in a brief intervention provided by novice therapists (n = 70). Additional measures will include traditional self-evaluations of competence, clinical confidence, and prior training and experience. Clients in the intervention study will be assessed using various process and symptom measures. Discussion This study aims to develop and validate the PBCT, a novel tool for assessing therapist competence. The PBCT is designed to reflect clinical skill development and knowledge on therapeutic change processes. It is expected to be sensitive to prior training and clinical experience, responsive to further training, and capable of detecting competence-outcome associations. The results are anticipated to contribute to intervention and dissemination science by providing empirical evidence on the importance of therapist training and competence. Trial registration The study is registered at: https://doi.org/10.17605/OSF.IO/B3A7D .